A pediatric case of primary ciliary dyskinesia caused by novel copy number variation in PIH1D3. Issue 5 (October 2022) - Xu, Yifei; Ogawa, Satoru; Adachi, Yuichi; Sone, Naoyuki; Gotoh, Shimpei; Ikejiri, Makoto; Nakatani, Kaname; Takeuchi, Kazuhiko
Abstract: An 11-month-old boy with productive cough was referred to our hospital. He had nasal obstruction immediately after birth, and wheezing, wet cough, and rhinorrhea were observed daily after the neonatal period. Clinical and imaging findings revealed secretory otitis media, chronic sinusitis, and bronchiectasis. Primary ciliary dyskinesia was suspected. Transmission electron microscopy of nasal cilia showed defects of the outer and inner dynein arms. Genetic examinations of the family revealed copy number variation in PIH1 domain-containing 3 ( PIH1D3 ) in the proband and mother. This is the first report of a Japanese patient with primary ciliary dyskinesia caused by copy number variation in PIH1D3.